chriscarlo1649
chriscarlo1649
04-04-2017
Mathematics
contestada
2a + 3b = 6
5a + 2b - 4 = 0
Respuesta :
Аноним
Аноним
04-04-2017
1 Solve for a in
2a+3b=6
a=3(2-b)/2
2 Substitute a=3(2-b)/2 into
5a+2b-4=0
15(2-b)/2+2b-4=0
3 Solve for b in
15(2-b)/2+2b-4=0
b = 2
4 Substitute b=2 into
a = 3(2-b)/2
a = 0
5 Therefore,
a=0
b=2
I hope this helps. :)
Answer Link
VER TODAS LAS RESPUESTAS ( 54+ )
ACCESS MORE
Otras preguntas
Answer those please and read the directions
Identify and explain ONE way the emergence of cities affected economic activities in early civilizations before 600 B.C.E
How can I solve this
The earth's radius is 6.37×106m; it rotates once every 24 hours. you may want to review ( pages 195 - 198) . part a what is the earth's angular speed
Can someone help me
The average full spreading rate over the last 20,000,000 years at placemark a in the red sea is _________. approximately 1 centimeter per year approximately 10
Recyclable or biodegradable packaging, recycled materials and components, and better pollution controls are ways that marketers have responded to the ________.
Nickel has a face-centered cubic unit cell with an edge length of 352.4 pm. Calculate the density of nickel
What happens to Dna during sexual reproduction
When water has a temperature greater than 100c?